PROPORSI MIKROSPORA UNINUKLEAT PADA EMPAT KLON TEBU (Saccharum spp.) - Suaib; Woerjono Mangoendidjojo; PDN Mirzawan; Ari Indrianto (The East Java Biological Society, 2007)
An experiment to study the two different morphological characters of four clones of sugarcane (Saccharum spp.) panicles containing more than 50% of uninucleate microspore development was conducted in Tissue Culture Laboratory at Biology Faculty, Gadjah Mada University, Yogyakarta, since March until May 2006. Morphological characters of both kinds of panicles i.e. unsheated- and sheated flowers from sheat flag leaf were observed. Mean, percentage, and standard deviation from the mean value of the six different stages of microspore development e.g. tetrad, early- and late-uninucleate, early- and late-binucleate, and multinucleate or pollen grains were statistically used in this calculation. All data percentages were analyzed by variance analysis through General Linier Model Procedure, and comparisons between means of the uninucleate microspore development based on the two different morphological characters of four clones was calculated by Least Significance Difference method. Comparisons between the two different panicles characteristics in accordance with the proportion of the uninucleate microspore development, however, were analyzed by T-student procedure. All calculations were done by using SAS program of computer statistics package. Result of the research showed that: (1) the unsheated panicles were contained less than 50% of uninucleate (early- and late-uninucleate) microspore development; (2) the sheated panicles tend to be in high proportion of early- and late-uninucleate microspore development, and multinucleate or pollen grains, and (3) the more away of spikelets or anthers positioned in the panicle or sub-panicle, the more number or percentage of uninucleate microspores development were tend to be gradually decreased.